Overinterpretation and Overtreatment of Low-Titer Antibodies Against Contactin-Associated Protein-2 - Bien, Christian G. (Frontiers in Immunology, 2018)
Antibodies against neural or glial antigens have become important diagnostic markers of autoimmune encephalitides. A key requirement for interpretation of any test in clinical medicine is specificity. In this work, a 35-year-old female patient with low-titer CASPR2 antibodies not satisfying clinical criteria of autoimmune encephalitis is reported. The patient had a recurrent depressive disorder and at the time of the antibody study a moderate depressive episode. Overinterpretation and misinterpretation of patient’s complaints and paraclinical study results fueled the idea of an autoimmune encephalitis. It is suggested to check patients with supposedly positive antibody test results critically for clinical criteria, titer cut-offs, and antibody-typical epidemiological features like age and sex.